Infusion methods of making of details are from pcm - Краля, В.О.; Джоган, О.М.; Костенко, О.П. (Proceedings of National Aviation University (archive), 2010)
Among a good deal of ways of part manufacturing from polymeric composite materials the infusion methods of impregnation of a fibre reinforcement on the mold are very popular now. Different schemes of impregnation of a fibre reinforcement, their features and ways of accelerated velocity of process are reviewed.